Abandoned! [electronic resource] : a narrative of the fearful adventure that befell a young man in the service of the Hudson Bay Co. - Andrews, Morgan ([S.l. : s.n., 1899)
From: The Wide World Magazine. Caption title. Electronic reproduction. Mode of access: Internet. 44